The anti-ableist manifesto : smashing stereotypes, forging change, and building a disability-inclusive world - Yu, Tiffany (Hachette Go, an imprint of Hachette Books, 2024)
"Tiffany Yu takes readers on a revelatory examination of disability -- how to unpack biases and build an inclusive and accessible world. As the Asian American daughter of immigrants, living with PTSD, and sustaining a permanent arm injury at age nine, Tiffany Yu is well aware of the intersections of identity that affect us all. She navigated the male-dominated world of corporate finance as an investment banker at Goldman Sachs before founding Diversability, an award-winning community business run by disabled people building disability pride, power, and leadership, and creating the viral Anti-Ableism series on TikTok. Organized from personal to professional, domestic to political, Me to We to Us, The Anti-Ableist Manifesto frames context for conversations, breaks down the language of ableism, identifies microagressions, and offers actions that lead to authentic allyship. How do we remove ableist language from our daily vocabulary? How do we create inclusive events? What are the advantages of hiring disabled employees, and what market opportunities are we missing out on when we don't consider disabled consumers? With contributions from disability advocates, activists, authors, entrepreneurs, scholars, educators, and executives, Yu celebrates the power of stories and lived experiences to foster the proximity, intimacy, and humanity of disability identities that have far too often been "othered" and rendered invisible." --